A "spatially just" transition? A critical review of regional equity in decarbonisation pathways. (June 2022) - Garvey, Alice; Norman, Jonathan B.; Büchs, Milena; Barrett, John
Abstract: Spatial justice is a theoretical framework that is increasingly used to examine questions of equity in the low carbon transition (LCT) from a geographical perspective. We conducted a semi-systematic review to define a 'spatially just' low carbon transition, considering how spatial dimensions are explicitly or implicitly presented in assessments of the LCT, and the policy and governance approaches that could embed spatial justice. A sample of 75 academic articles was thematically coded. Spatial justice involves the fair distribution of both benefits and burdens associated with LCTs, and this often creates problems of equity given the geographic gap between regions that 'win and lose'. The studies point to a research gap in exploring fairness implications that go beyond the employment impacts of transition. Acceptance of the LCT is shown to be contingent on perceptions of justice, particularly whether the most responsible and capable actors are taking action. There is similar concern that the LCT may not address, or may reproduce, existing patterns of injustice. This is particularly the case in terms of spatially inequitable land uses and where historic planning policy has had lasting socioeconomic impacts. Policy challenges to making LCTs more spatially just included administrative fragmentation across spatial scales and the lack of coordination in net zero policy. We identify that future transition policymaking could benefit from using spatially targeted interventions, and in adopting a whole systems approach. In this recognition of the multiple economic vulnerabilities of different regions, LCT policymaking can become both more effective and, critically, more just. Highlights: Spatial justice considers the fair geographic distribution of benefits and burdens. We conducted a semi-systematic review and thematic coding of 75 academic articles. Acceptability in the low carbon transition is dependent on perceived justice. Whole systems and embodied justice approaches were seen as more spatially just. Spatially targeted policies, devolved powers and targets were viewed as solutions.